(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Microfinance is considered as an important contribution to improve the standard of living of poor people to eradicate poverty in rural areas. Microfinance is the need of the hour with a focus on rural areas to enhance their infrastructure and improve the economic conditions of the poor. Efforts should be made to improve the economic conditions of women in rural areas by participating in self-help groups and providing microfinance. For the overall development of the rural areas, it is the need of the time to try to bring the economically disadvantaged groups into the stream of economic development through micro finance initially and to provide them with an ideal finance supply at low interest rate for the future by taking incentive programs to set up small enterprises.